Altered myocardial acetylcholine and norepinephrine concentrations in right ventricular hypertrophy and failure - Yamada, Y; Okumura, K; Hashimoto, H; Ito, T; Satake, T (Heart and vessels, 1991)
The progression of cardiac hypertrophy and failure is associated with marked changes in cardiac autonomic innervation, and there are sympathetic-parasympathetic interactions in the regulation of cardiac function. Although the indexes of sympathetic innervation have been found to be depressed with the development of heart failure, those of parasympathetic innervation have not yet been fully investigated. In order to better understand changes in markers of autonomic innervation associated with cardiac hypertrophy and failure, we measured the myocardial acetylcholine (ACh) store as a parasympathetic marker and the norepinephrine (NE) store as a sympathetic marker in pressure-overloaded right ventricular hypertrophy in rats. Two weeks after the injection of monocrotaline, significant right ventricular hypertrophy occurred. Three weeks after, severe right ventricular hypertrophy with no sign of heart failure occurred, and 4 weeks after, overt heart failure developed. In the right heart of monocrotaline rats, NE concentrations tended to increase at 1 week, returned to baseline at 2 weeks, decreased to one-half of the control values at 3 weeks, and then fell to 14% of the controls at 4 weeks. ACh concentrations in the right heart tended to increase at 1 week and exhibited a significant increase (136% and 129% of the controls in the right atrium and ventricle, respectively) at 2 weeks. As with NE, ACh concentrations in the right atrium and ventricle decreased to 76% and 54% of the controls at 3 weeks, and continued to decrease to 22% and 24% of the controls at 4 weeks after monocrotaline.